Effective composting process for lignocellulosic materials from agro-industrial waste in Malaysia - Chai, Ee Wen (2015)
Excessive chemical fertilising to soil will compromise future food production by degrading soil fertility. Organic fertilisers in the form of compost provide increased physical and biological storage mechanisms to soils, mitigating risks of over-fertilisation. However, lignocellulosic materials composting require long time to reach maturation. This study was aimed to develop an effective composting process of lignocellulosic materials from agro-industrial wastes in Malaysia. The study started from the selection of feedstock and microorganisms for composting, followed by the determination of most suitable composting environment conditions for microorganisms to degrade the selected compost feedstock. In this study, the effect of moisture content and turning frequency of composting on maturity and quality of compost feedstock were determined. Once the composting parameters are determined, the biodegradation rate of organic substances in selected compost feedstock was evaluated. Through the biodegradation rate of organic substances in selected compost feedstock, the compost feedstock can be mixed together to have effective biodegradation. The C/N ratio of compost was adjusted by having different mixing ratios of the selected compost feedstock for composting process. During composting, temperature, moisture content, pH, oxygen concentration, and colour changes were monitored while total nitrogen, total organic carbon, total organic matter, C/N ratio, chemical composition and colony forming unit were evaluated weekly to draw the trends of these substances over composting time. From the results, empty fruit bunches (EFB), coffee ground and palm oil mill sludge (POMS) were selected as compost feedstock to represent material with the high, ideal and low C/N ratio,respectively. The ratio of 60% of Bacillus subtilis and 40% of Aspergillus niger showed higher cellulose degradability in filter paper was selected as the best fungus and bacterium ratio for composting. Moisture content of the compost pile should be controlled between 50- 60% throughout the composting period. On the other hand, the measured oxygen concentration was significantly higher by increase the turning frequency in the coffee ground due to the low bulk density and vigorous microbial activity in the compost piles. It was also found out that the moisture content on the surface of compost piles dropped below 50% in 14 days with compost piles without turning and turning every 9 days. Thus,turning every 6 days on the compost piles was selected as the most practical turning frequency for the EFB, coffee ground and POMS. The study on biodegradation rate of organic substances in the compost feedstock providesinformation on the composting stages and indicated the selected compost feedstock should be mixed together to enhance the biodegradation rate. Through co-composting, different mixing ratios of selected compost feedstock were composted and C/N ratio of compost piles dropped to 20 in 8 weeks. As a conclusion, effective composting process for EFB, coffee grounds and POMS was developed with 60% of Bacillus subtilis and 40% of Aspergillus niger, the compost piles should control between 50- 60%, turn the compost pile every 6 day, and through co-composting method.